Pendampingan Blended Learning Berorientasi Pada Kemampuan Literasi dan Numerasi Pasca Pandemi Covid-19 di SDN 2 Tanjungpura - Siti Sahronih; Endang Pujiastuti (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic has several impacts on the world of education including dropout rates, decreased learning achievement, and violence in children, as well as external risks. Based on some data, the impact of Covid-19 also causes loss generation, so it is necessary to hold a mentoring program to overcome motivation and participant loss in face-to-face and online learning that must be implemented by some schools. Indramayu is one of the areas that are at level 3 and according to The Ministry of Home Affairs, No.30 of 2021 has been able to carry out face-to-face learning. The implementation of face-to-face learning provides several solutions ranging from reflection to follow-up plans, in addition, face-to-face learning also allows for blended learning. The steps in this program include: (1) technical guidance activities and coordination of activities; (2) the preparation of work plans and the development of numeracy literacy instruments and psychosocial instruments; (3) preparation of guidebooks and modules and coordination with the school. The results of the initial and final assessment analysis for students, teachers, and parents at SDN 2 Tanjungpura showed that the program was carried out well with data as many as 98% of students felt excited and enjoy participating in mentoring activities through the establishment of progressive matching environmental. Keywords: Covid-19 pandemic, blended learning, literacy skill, numeracy skill, primary school